Arctic Service Test of XM237 Mounting Kit, Vehicle, Guided Missile System (Ready-Rack) for REDEYE Weapons - Stephens, Jr, James A (1969)
An Arctic Service Test of the modified XM237, Mounting Kit, Vehicle, Guided Missile System (Ready-Rack) was conducted by the Air Defense Board at Fort Greely, Alaska, from 14 through 24 January 1969. The Arctic Service Test was conducted to determine the suitability of the Ready-Rack in an arctic field environment. The Ready-Rack was exposed to prevailing arctic conditions for a period of 8 days at ambient air temperatures ranging from -3 deg F to -53 deg F. During the testing period the Ready-Rack was transported a total of 957.6 miles. Testing revealed that even though the latch and clamp assemblies are more durable than those used in the temperate test, interference still exists between the clamp bands, and the latch fastener hole still enlarges from erosion.